Renewable energy as an alternative source for energy management in agriculture - Majeed, Yaqoob; Khan, Muhammad Usman; Waseem, Muhammad; Zahid, Umair; Mahmood, Faisal; Majeed, Faizan; Sultan, Muhammad; Raza, Ali (Energy reports, 2023)
This study provides a high-level overview of alternative energy sources that can be harnessed to power agricultural operations, focusing on renewable energy technologies. When thinking about the overall economy around the globe, agriculture is vital. Energy is required at each step of production, from fertilizer production to fueling tractors for planting and harvesting. The high energy prices and unpredictable energy market significantly affect the input energy costs. Energy efficiency methods, when properly applied, and the use of farm’s renewable energy sources could assist agricultural producers in saving energy-related costs. Renewable energy resources in the form of solar, biomass, wind, and geothermal energy are abundantly available in the agriculture sector. This review aims to explore renewable energy as an alternative energy source for efficient energy management in agriculture. It discusses the potential benefits, challenges, and opportunities associated with adopting renewable energy technologies in the agricultural sector. Our research adds value by presenting a comprehensive overview of alternative energy sources and their applicability in energy management. By highlighting the benefits and potential challenges associated with each option, we provide valuable insights for agricultural stakeholders and researchers aiming to transition toward sustainable energy practices in the sector. Better energy management is intertwined with problems that need a broader strategy than has so far been used. In a nutshell, transitioning to alternative energy sources for energy management in agriculture holds great promise for reducing greenhouse gas emissions, improving energy efficiency, and promoting sustainability in food production. However, successful implementation requires addressing technical, economic, and policy barriers while fostering knowledge dissemination and capacity building among farmers and stakeholders.